The Effect Of Hypertension Exercise On Reducing Blood Pressure In The Elderly In Work Area Puskesmas Simpang Dolok District North Sumatra Coal Year 2023 - Srimis Leini Saragih (Sean Institute, 2023)
above normal indicated by systolic numbers (top) and diastolic numbers. In North Sumatra, according to Riskesdas 2019 pravalence was 7,4% of the total population and ranked fourth out of ten non-communicable diseases. This study aims to determine the effect of elderly gymnastics on the decrease in blood pressure in people with hypertension in Subdistrict, Puskesmas Simpang Dolok Kabupaten Batu Bara Sumatera Utara Years 2023. Research using Pre Experiment One Group Pre and Posttest design. The population of all hypertensive patients in the area of puskesmas often in month September until Nopember yearst 2022 87 people. Technique of sampling that is Purposive Sampling with amount as many as 10 people. Data collection was done with observation sheet, blood pressure checking tool, data analysis was done with Independent T test. The result of the research before the elderly gymnastics of the majority of hypertension degree 1, after the normal elderly hypertension gymnastics, Independent T test, obtained the mean (mean) before the elderly gymnastics 146.00 mmHg, and after ugly gymnastics 116.00 mmHg, p value of 0,000 which means p value <0.05, t value = 11.619. Based on the results of this study it can be concluded that there is influence of elderly gymnastics to the decrease of blood pressure in Sering District Public Health Center Simpang Dolok Kabupaten Batu Bara Sumatera Utara Year 2023. It is suggested to further researcher to develop method in lowering blood pressure in hypertension patient besides using elderly gymnastics zikir